Prediagnostic telomere length and risk of B‐cell lymphoma—Results from the EPIC cohort study. Issue 12 (12th May 2014) - Hosnijeh, Fatemeh Saberi; Matullo, Giuseppe; Russo, Alessia; Guarrera, Simonetta; Modica, Federica; Nieters, Alexandra; Overvad, Kim; Guldberg, Per; Tjønneland, Anne; Canzian, Federico; Boeing, Heiner; Aleksandrova, Krasimira; et al.
<x xml:space="preserve">Abstract</x> Recent epidemiological investigations have reported on the association between telomere length (TL) and a number of malignancies, including B‐cell lymphoma (BCL). The reported results for BCLs are however inconsistent. We carried out a nested case–control study to determine whether TL is associated with future risk of BCL. Using quantitative polymerase chain reaction, the relative TL (i.e. the ratio of telomere repeat copy number to single gene copy number) was measured in mononuclear cell DNA of prediagnostic peripheral blood samples of 464 lymphoma cases and 464 matched controls (median time between blood collection and diagnosis, 4.6 years). Conditional logistic regression was used to analyze the association between TL and the risk of developing lymphoma and histologic subtypes. TL was significantly longer in cases compared to controls (p = 0.01). Multivariable models showed a significantly increased risk of BCL [odds ratio (OR) = 1.66, 1.80 and 3.20 for quartiles 2–4, respectively, p‐trend = 0.001], diffuse large B‐cell lymphoma (DLBCL) (OR = 1.20, 2.48 and 2.36 for quartiles 2–4, respectively, p‐trend = 0.03) and follicular lymphoma (FL) (OR = 1.39, 1.90 and 2.69 for quartiles 2–4, respectively, p‐trend = 0.02) with increasing TL. This study suggests an association between longer leucocyte TL and increased risk of BCL which was most pronounced for DLBCL and FL.